Peak timing in two dialects of Connaught Irish - NI CHASAIDE, AILBHE (My University, 2005)
A comparison of the peak location in nuclear and initial prenuclear accents was carried out for two closely related dialects of Connaught Irish: Cois Fharraige and Inis Oirr. This was done across conditions where the number of unstressed syllables following the nuclear and preceding the initial prenuclear accents was varied from 2-0. Clear differences in peak timing emerged between the two dialects. In Cois Fharraige Irish the timing of the peak is unaffected by the presence and/or number of adjacent unstressed syllables. In Inis Oirr Irish there is variability in peak timing for both prenuclear and nuclear positions. In nuclear position Inis Oirr peak realizations for the different conditions range from the left edge of the accented vowel to the post accented vowel. In prenuclear position realizations range from the left-edge of the accented vowel as far as the right edge of the post accented syllable
Proceedings of the 9th European Conference on Speech Communication and Technology
INTERSPEECH 2005
PUBLISHED
Lisbon
Keywords: Computer science